2010
DOI: 10.1111/j.1365-2966.2010.17475.x
|View full text |Cite
|
Sign up to set email alerts
|

First Kepler results on compact pulsators - V. Slowly pulsating subdwarf B stars in short-period binaries

Abstract: The survey phase of the Kepler Mission includes a number of hot subdwarf B (sdB) stars to search for non‐radial pulsations. We present our analysis of two sdB stars that are found to be g‐mode pulsators of the V1093 Her class. These two stars also display the distinct irradiation effect typical of sdB stars with a close M‐dwarf companion with orbital periods of less than half a day. Because the orbital period is so short, the stars should be in synchronous rotation, and if so, the rotation period should imprin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
52
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 59 publications
1
52
0
Order By: Relevance
“…In the first four quarters of the Kepler mission, a survey for pulsating stars was made, and a total of 113 compact-pulsator candidates were checked for variability by Østensen et al (Østensen et al 2010b;2011 = Paper I). This very successful survey revealed one clear V361-Hya pulsator (Kawaler et al 2010b) and one other transient short-period pulsator, and a total of thirteen V1093-Her stars (Reed et al 2010;Kawaler et al 2010a;Baran et al 2011, Paper II), including an sdB+dM eclipsing binary in which the hot primary shows an exceptionally rich pulsation spectrum (Østensen et al 2010a). Another three V1093-Her pulsators have been identified in the open cluster NGC 6791 (Pablo et al 2011;Reed et al 2012a), bringing the total number of sdBV stars in the Kepler field to eighteen.…”
Section: Introductionmentioning
confidence: 99%
“…In the first four quarters of the Kepler mission, a survey for pulsating stars was made, and a total of 113 compact-pulsator candidates were checked for variability by Østensen et al (Østensen et al 2010b;2011 = Paper I). This very successful survey revealed one clear V361-Hya pulsator (Kawaler et al 2010b) and one other transient short-period pulsator, and a total of thirteen V1093-Her stars (Reed et al 2010;Kawaler et al 2010a;Baran et al 2011, Paper II), including an sdB+dM eclipsing binary in which the hot primary shows an exceptionally rich pulsation spectrum (Østensen et al 2010a). Another three V1093-Her pulsators have been identified in the open cluster NGC 6791 (Pablo et al 2011;Reed et al 2012a), bringing the total number of sdBV stars in the Kepler field to eighteen.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Pablo et al (2011) were able to infer a rotation period of 9.63 days of the primary from the characteristic even splitting of the pulsation periods, thereby demonstrating that the rotation of the primary is not synchronised with the orbital period. More recently Pablo et al (2012) have demonstrated that the same is the case for both of the long-period pulsators of Kawaler et al (2010a). Long-period pulsations have also been reported from ground-based studies of the sdB+dM binary GALEX J0321+4727, which has an orbital period of 0.266 d .…”
Section: Introductionmentioning
confidence: 63%
“…Recently, a fourth sdB+dM binary with a pulsating primary was revealed in Kepler data by Pablo et al (2011). This system with an orbital period of 0.399 d is very similar to the two systems presented by Kawaler et al (2010a), but is a member of the open cluster NGC 6791. Interestingly, Pablo et al (2011) were able to infer a rotation period of 9.63 days of the primary from the characteristic even splitting of the pulsation periods, thereby demonstrating that the rotation of the primary is not synchronised with the orbital period.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Kawaler et al (2010) found two compact binaries with gravity-mode pulsations superposed to an irradiation effect typical of sdB stars with a close M-dwarf companion. The orbital periods are less than half a day such that seismic sounding should become possible in the future, once the noise level of the data can be brought down to such a level that tidal and/or rotational splitting can be disentangled from period spacings of the modes.…”
mentioning
confidence: 99%